Pengaruh Modal Dan Sikap Kewirausahaan Terhadap Pendapatan Pedagang Di Pasar MMTC Medan - Lumban Gaol, Dody Harianto; Sihombing, Natalia E.; Rajagukguk, Jonson (Research and Community Service UNIVERSITAS KALBIS, 2025)
This study aims to determine how Capital and Entrepreneurial Attitude Influence Traders' Income in MMTC Market Medan. This study uses a quantitative approach and uses data collection techniques by distributing questionnaires. Hypothesis testing in the partial test section (t test) obtained a calculated t value on the capital variable of 3,252 where the value is> 1.66 and the significant value of the capital variable is 0.000 <0.05 and the calculated t on the entrepreneurial attitude variable is 1,235 where the value is> from the t table which is 1.66 and the significant value of the entrepreneurial attitude variable is 0.000 <0.05. Then H0 is rejected H1 is accepted so based on these results it can be concluded that capital and entrepreneurial attitudes have a significant effect on income variables. And in the simultaneous test (F test) the calculated F value is 173,395 where> from the F table of 3.10 it can be concluded that the Capital and Entrepreneurial Attitude variables together have a significant effect on Income.